(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article discusses interdisciplinary connections in the lessons of the Russian language in the Uzbek school. Various approaches to the classification of intersubject relations are given. The specifics of studying the Russian language in an Uzbek school are revealed. Groups of corresponding speech skills are characterized.